Validated Outcome Measures and Postsurgical Scar Assessment Instruments in Auricular Surgery: A Systematic Review. Issue 7 (July 2021) - Chu, Sherman; Ramanathan, Diya; Thuener, Jason E.; Carroll, Bryan T.
Abstract : BACKGROUND: The utilization of an assessment instrument that successfully analyzes validated outcome measures for auricular surgery is important for advancing evidence-based medicine. OBJECTIVE: To systematically review postsurgical scar assessment instruments and outcome measures after auricular surgery to assess if any individual or combination of 2 assessment instruments encompass all relevant, validated auricular outcome measures. METHODS: Two systematic reviews were conducted using the PubMed/MEDLINE and Ovid databases: one for postauricular surgical outcome measures and another for postsurgical scar assessment instruments. Auricular outcome measure articles were selected for inclusion if they included at least one auricular-specific validated outcome measure, and assessment tool articles were included if they referenced one or more specific tool(s) specifically designed to assess postsurgical scars. Assessment tools were evaluated based on which outcome measures each covered. RESULTS: There was no single postsurgical scar assessment instrument or combination of 2 instruments that covered all outcome measures within the 5 different categories (psychosocial well-being, functional, objective appearance, subjective appearance, and clinical-related outcomes) after auricular surgery. None of the instruments measured functional outcomes, such as the ability to wear glasses and hearing outcomes. CONCLUSION: There is currently no existing postsurgical scar assessment instrument that covers all outcome measures after auricular surgery. Abstract : Supplemental Digital Content is Available in the Text.